2014
DOI: 10.1261/rna.040980.113
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous U2·U5·U6 snRNA complexes in S. pombe are intron lariat spliceosomes

Abstract: Excision of introns from pre-mRNAs is mediated by the spliceosome, a multi-megadalton complex consisting of U1, U2, U4/U6, and U5 snRNPs plus scores of associated proteins. Spliceosome assembly and disassembly are highly dynamic processes involving multiple stable intermediates. In this study, we utilized a split TAP-tag approach for large-scale purification of an abundant endogenous U2·U5·U6 complex from Schizosaccharomyces pombe. RNAseq revealed this complex to largely contain excised introns, indicating tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 65 publications
9
51
0
Order By: Relevance
“…A previous study identified an interaction between S. cerevisiae Drn1 and the Nineteen Complex component Ntc40/Cwc2 (Hazbun et al 2003); paralogs of Drn1 in S. pombe (Cwf19p and Mug161p) copurify with Nineteen Complex components (Ohi et al 2002;Ren et al 2011;Chen et al 2014); and human Drn1 paralogs (Cwf19l1 and Cwf19l2) copurify with spliceosomes (Rappsilber et al 2002).…”
Section: Drn1 Interacts With Spliceosomal Components and Branched Rnamentioning
confidence: 93%
“…A previous study identified an interaction between S. cerevisiae Drn1 and the Nineteen Complex component Ntc40/Cwc2 (Hazbun et al 2003); paralogs of Drn1 in S. pombe (Cwf19p and Mug161p) copurify with Nineteen Complex components (Ohi et al 2002;Ren et al 2011;Chen et al 2014); and human Drn1 paralogs (Cwf19l1 and Cwf19l2) copurify with spliceosomes (Rappsilber et al 2002).…”
Section: Drn1 Interacts With Spliceosomal Components and Branched Rnamentioning
confidence: 93%
“…An alternative to enriching for lariats by stabilization is to enrich for lariats by coimmunoprecipitation with the spliceosome; in extracts from wild-type cells, immunoprecipitation of endogenous spliceosomes coprecipitates lariats (e.g., Small et al 2006;Chen et al 2014). To test whether lariat enrichment by immunoprecipitation of the spliceosome enables the application of LIT-seq to wild-type cells, we immunoprecipitated spliceosomes using antibodies against Prp16, one of the factors that associates with the spliceosome at the lariat intermediate stage and through coimmunoprecipitation enriches for lariat intermediates (Schwer and Guthrie 1991).…”
Section: Lit-seq Can Be Applied To Wild-type Cellsmentioning
confidence: 99%
“…S7). Because endogenous spliceosomes have been immunopreciptated previously from other organisms, such as human cells (e.g., Girard et al 2012), and transcripts bound to endogenous spliceosomes have already been identified (Volanakis et al 2013;Chen et al 2014;Nojima et al 2015), we anticipate that LIT-seq can be applied broadly to other organisms to efficiently, specifically, and directly monitor splicing site choice genome-wide and with single-nucleotide resolution.…”
Section: Future Applications Of Lit-seqmentioning
confidence: 99%
“…RNA-RNA interactions are mainly responsible in spliceosome remodeling and catalytic core conformation [11][12][13] and numerous proteins are also required for assembly and splicing catalysis and splicing fidelity as well [14][15][16]. Participating factors of mainly human and yeast have been determined by mass spectrometry (MS) of in vitro assembled and affinity-purified spliceosomal complexes of model pre-mRNAs [17][18][19][20][21][22][23][24][25][26][27][28][29]. Over 150 proteins have been recruited in such complexes and this repertoire has been extended when the analysis was carried out from yeast, human and chicken cellular spliceosomes [30].…”
Section: Introductionmentioning
confidence: 99%